The −675 4G/5G PAI-1 polymorphism confers genetic susceptibility to systemic lupus erythematosus, its clinical manifestations, and comorbidities in Mexican-Mestizo population - B. U. Anaya-Macias; U. De la Cruz-Mosso; C. A. Palafox-Sánchez; I. Parra-Rojas; G. Martínez-Bonilla; L. González-López; J. I. Gámez-Nava; E. E. Pérez-Guerrero; S. L. Barrientos-Avalos; J. F. Muñoz-Valle (Taylor & Francis Group, 2020)
Systemic lupus erythematosus (SLE) involves a broad range of factors that contribute to the development of the disease and its comorbidities. Genetic predisposition influences the development of SLE, and the −675 4G/5G PAI-1 polymorphism has been associated with several pathologies with a chronic inflammatory component. Our objective was to investigate the genetic association between the −675 4G/5G PAI-1 polymorphism with SLE, its clinical manifestations, and comorbidities in a Mexican-Mestizo population. The −675 PAI-1 polymorphism was determined by PCR-RFLP in 716 subjects: 293 SLE patients and 423 control subjects. Significant associations for SLE genetic susceptibility were found in carriers of 4G/5G (OR = 2.63; CI 1.81-3.87; p < .001) and 4G/4G (OR = 2.70; CI 1.62-4.51; p < .001) genotype in comparison with the 5G/5G genotype; 4G allele carriers also presented genetic risk for SLE (OR = 1.63; CI 1.31-2.03; p < .001) compared to the 5G allele. Following a dominant genetic model, a similar association was found with the 4G allele to SLE (OR = 2.66; CI1.84-3.84; p < .001). The 4G/5G genotype was associated with shorter disease duration (p = .039), as well as lower levels of haemoglobin (p = .001) and haematocrit (p = .009); the need for prednisone treatment (p = .001), higher BMI (p = .03), presence of type 2 DM (p = .015), clinical activity (Mex-SLEDAI = 57%; p = .047), Chronicity (SLICC-ACR = 0; p = .015) and CRP levels (p = .015) were associated with 5G/5G genotypes. In conclusion, the −675 4G/5G and 4G/4G PAI-1genotypes were found as genetic risk markers of susceptibility for SLE in the Mexican-Mestizo population, and each genotype could influence the clinical manifestations and comorbidities differently in SLE.